PREVALENCE OF HYPODERMA BOVIS AND THE ECONOMIC LOSSES CAUSED BY THE INFESTATION IN CATTLE HIDES - Mallah, Mohammed Awad; Rahif, Raad Harbi (The Iraqi Journal of Veterinary Medicine, 2003)
One thousand nine hundred thirty three cattle were examined, at age six months – eight years, slaughtered at Al-Shuala abattoir and market for selling the animals and also cows reared in 7 Nissan plan in Al-Ameria research plan belonging to IBA center for agricultural research, for a period extended from September 2001 until June 2002. The results of the study showed that the rate of infestation with Hypoderma bovis was 10.34% and the larvae were found in November and the higher rate of infestation was in December and reached 23.5%, while the lower rate was in May and reached 3.7%. Animals at age of 3-< 5.5 years showed the higher rate of infestation and reached 13.28% while others at age of 5.5 – 8 years showed the lower rate of infestation and reached 8.75% with significant difference (P< 0.05). The economic losses caused by infestation with Hypoderma bovis were evaluated. In Al-Shuala slaughterhouse infestation ranged from low intensity (1-5 bores) and it’s higher rate was 25.9% in November, to moderate (6-10 bores) with the rate 13.9% and high (>10 bores) and its rate 6.3% in January. The over all losses were 859945.95Dinars. In Al-Karkch abattoir the higher rate of low intensity was 17% in January, the moderate infestation was 13.3% in November and the high intensity was 12.1% in January and the overall losses caused by different degree of infestation was 1177618.55 Dinars. A higher low rate 15%, moderate 10% and high 5% infestation were found in November and the overall losses reached 329450.75 Dinars .The study didn’t show any losses in 7 Nissan and Al-Ameria Research plans and Veterinary Medicine College farm.